The Importance of Expertise Visibility Across Organizational Boundaries for Individual Performance. Issue 1 (2nd January 2020) - Poleacovschi, Cristina; Javernick-Will, Amy
Abstract: The importance of knowledge sharing within engineering organizations is well acknowledged within the literature. A critical step to organizational knowledge sharing involves expertise visibility, or knowing who knows what, as employees must first identify who has the knowledge needed for project or organizational tasks before engaging in knowledge exchange. Thus, expertise visibility is theorized to improve group and organizational performance; however, there is a dearth of literature that has analyzed the importance of expertise visibility on employee performance. Due to the importance of employee performance for group and organizational performance, this research analyzed the relationship between expertise visibility and employee performance. Specifically, we analyzed responses to survey questionnaires to compare visibility across organizational boundaries with employee performance using social network analysis and linear regression analysis. Results showed that being visible across technical expertise, office, and hierarchy boundaries were associated with increased employee performance. Engineering organizations can use these results to encourage and incentivize employees to become more visible outside of their immediate groups in order to increase their performance. The paper contributes to theory of transactive memory by showing the importance of expertise visibility for performance at the individual level.